Determinants of Profitability of Insurance Companies in Syria - حيدر, حيدر (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The purpose of this study is to determine the main internal factors affecting profitability of Syrian insurance companies listed at Damascus Securities Exchange. The study used data from annual financial reports over the period 2009-2021. Profitability was measured by return on assets and five internal factors were investigated premium growth ratio, share of reinsurance, solvency margin, combined ratio, and size. ROA was regressed against internal factors using weighted least squares method. Results showed that premium growth rate, combined ratio, and size significantly affected profitability of insurance companies, whereas the effect of reinsurance share and solvency margin was not statistically significant over the studied period. Insurance companies' management should make more efforts to expand their insurance activities taking into consideration the level of insured risks. الكلمات المفتاحية: شركات التأمين السورية، الربحية، العوامل الداخلية، طريقة المربعات الصغرى الموزونة. Keywords: Syrian insurance companies, profitability, internal factors, WLS.